Exploring the Role of Estrogens in Lizard Spermatogenesis through the Study of Clomiphene and FSH Effects - Mariailaria Verderame; Rosaria Scudiero; Ermelinda Limatola (International Journal of Endocrinology)
Spermatogenesis is a fascinating biological process aiming to generate haploid spermatozoa from diploid spermatogonia through a specific hormonal network between gonadotropins and steroids. Increasing evidence suggests that the primary female sex hormone estrogen plays an active role in this process. This research points out on the role of estrogen during lizard spermatogenesis by using three experimental approaches: (1) exposure to an analogue of nonsteroidal estrogen as Clomiphene citrate that acts both as estrogen agonist and antagonist; (2) exposure to the gonadotropin FSH; and (3) exposures to FSH followed by Clomiphene. Histological and immunohistochemical results demonstrate that in the lizard Podarcis sicula during the mating period, Clomiphene as well as FSH determines the breakdown of spermatogenesis and the epididymal regression, presumably through estrogens input as indirectly demonstrated by the appearance of ERα and vitellogenin in the liver. The ability of Clomiphene to restore the gonadal natural condition after FSH treatment is also demonstrated. Finally, data indicate that lizard testis and epididymis control their morphophysiology regulating the intracellular presence of ERα.